New records of false spider mites (Acari: Trombidiformes: Tenuipalpidae) in Greece - Stathakis, Theodoros I.; Vrettos, Dimitrios P.; Panou, Eleni N.; Kapaxidi, Eleftheria V. (Zootaxa, 2023)
Two false spider mite species (Tetranychoidea: Tenuipalpidae) are reported in Greece. One new species, Aegyptobia insularis Stathakis and Vrettos sp. nov., collected from the Mediterranean shrub Phagnalon rupestre ssp. graecum (Asteraceae), is described. Dolichotetranychus summersi Pritchard and Baker is found on a new and probably natural host plant, the common couch grass Elymus repens (Poaceae); this is the first record of this mite in the Palearctic region. Females and deutonymphs of D. summersi are redescribed, based on the specimens from Greece.